PENGARUH GAYA KEPEMIMPINAN HINDU DAN PENGETAHUAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI PEMODERASI PADA INDUSTRI KECIL DAN MENENGAH DI KOTA DENPASAR - Ida Ayu Sasmita Dewi; Ni Wayan Alit Erlinawati; Ni Wayan Yuniasih (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
This study aims to determine the effect of Hindu leadership style, accounting knowledge on the use of accounting information, and environmental uncertainty in moderating the influence of leadership style and accounting knowledge on the use of accounting information. The problems raised in this study are, 1) whether Hindu leadership style influences the use of accounting information in small and medium industries (SMIs) in Denpasar City, 2) whether accounting knowledge influences the use of accounting information in SMIs in Denpasar City, 3) whether environmental uncertainty moderates the relationship of Hindu leadership style to the use of accounting information in SMIs in Denpasar City, 4) whether environmental uncertainty moderates the relationship of accounting knowledge to the use of accounting information in SMIs in Denpasar City. The population in this study were the owners of small and medium industries (SMIs) in the city of Denpasar. Determination of the sample used in this study was purposive sampling technique. Data collection techniques used in the form of observations, questionnaires, and interviews. The method of data analysis in this study used the research instrument test, interval succession method, classic assumption test, moderated regression analysis (MRA) test, model feasibility test and hypothesis test. The results of the study that Hindu leadership style and accounting knowledge influencesthe use of accounting information. Environmental uncertainty is also not able to moderate the relationship of Hindu leadership style and accounting knowledge to the use of accounting information. Every business decision mostly uses accounting information as its source. This causes the use of accounting information not to depend on the accounting knowledge of the company owner. In addition, business decisions are often not only made by company owners but also consider input from staff who may have more accounting knowledge